1986
DOI: 10.1111/j.1432-1033.1986.tb09795.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mr‐50000 polypeptide of mammalian pyruvate dehydrogenase complex participates in the acetylation reactions

Abstract: The mammalian pyruvate dehydrogenase complex, M , 8.5 x lo", contains an additional tightly bound 50 000-M , polypeptide, Component X, which copurifies with the intact assembly.Small amounts of the individual E2 and X polypeptides were obtained by elution of the protein bands from SDS/polyacrylamide gels. One-dimensional peptide mapping studies with ' 251-labelled lipoyl acetyltransferase (E2) and component X subunits indicate that these two proteins are structurally distinct entities. Similar analysis of puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Interestingly, the abnormality present in E2 affects measurable transacetylase activity but those in protein X do not. This suggests that X itself does not contribute significantly to the cellular dihydrolipoyl transacetylase activity despite the fact that the lipoyl groups on X can be acetylated (1,2). Ifthe PDH complex could be purified from patient derived cell lines in sufficient quantity to allow detailed study more information could be gained about the role ofthe two lipoyl proteins in the complex.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, the abnormality present in E2 affects measurable transacetylase activity but those in protein X do not. This suggests that X itself does not contribute significantly to the cellular dihydrolipoyl transacetylase activity despite the fact that the lipoyl groups on X can be acetylated (1,2). Ifthe PDH complex could be purified from patient derived cell lines in sufficient quantity to allow detailed study more information could be gained about the role ofthe two lipoyl proteins in the complex.…”
Section: Resultsmentioning
confidence: 94%
“…This protein, whose mobility on sodium dodecyl sulfate polyacrylamide gels is slightly greater than the E3 component lipoamide dehydrogenase (Mr = 53,000), resembles the E2 dihydrolipoyl tranacetylase protein in that it bears a lipoyl group attached to a lysine residue (3,4). This lipoyl residue is capable of being acetylated when the complex is treated with pyruvate (1,2), though protein X itself has no innate dihydrolipoyl transacetylase activity. The study of human pyruvate dehydrogenase complex deficiency has shown that defects in the El compo-nent are most common, with a smaller number of E3 defects (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both E2 and protein X participate in the acetylation reactions of the complex [6] and apparently act as independent substrates for reductive acetylation by pyruvate dehydrogenase (El) [23]. The inability to dissociate protein X from the E2 core assembly except under denaturing conditions also highlights the close physical and functional integration of these two components [3].…”
Section: Organisation Origins and Function Of Protein Xmentioning
confidence: 99%
“…In the native complex, 20-30 ce2B2 tetramers of pyruvate dehydrogenase, E1 (EC 1.2.4.1) and 6 homodimers of dihydrolipoamide dehydrogenase, E3 (EC 1.8.1.4) are attached non-covalently to a multimeric core assembly of 60 lipoic acid-containing acetyltransferase (E2) subunits (EC 2.3.1.12), organised in the form of a pentagonal dodecahedron [1,2]. Attention has also focused on a minor core species, protein or component X [3,4], a distinct lipoylbearing polypeptide [5] which is tightly-bound to E2 and also participates in the acetylation reactions of the complex [6].…”
Section: Introductionmentioning
confidence: 99%